2018
DOI: 10.1155/2018/6018613
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effects of Marble Powder Amount on the Self‐Compacting Concretes Properties by Microstructure Analysis on Cement‐Marble Powder Pastes

Abstract: The marble powder (MP), obtained from waste sludge marble processing, has a high specific surface area; this could mean that it can be used as filler added to self-compacting concrete (SCC). The aim of this experimental work is to study the effects of the cement-MP paste volume on the rheology in the fresh state and the hardened properties (compressive strength) of SCC by a microstructure analysis on paste samples with different amounts of MP. For all pastes, the morphological forms and the chemical compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The finer particle size leads to a denser microstructure, which ultimately increases the strength. The filler effect of marble powder is also confirmed by Alyousef et al while using it in self-compacting concrete [22]. Riaz et al carried out a similar study, involving the use of a fine filler material in place of clay in fire-burnt clayey bricks: They have observed similar increase in compressive strength of the finished blocks [23].…”
Section: Resultsmentioning
confidence: 72%
“…The finer particle size leads to a denser microstructure, which ultimately increases the strength. The filler effect of marble powder is also confirmed by Alyousef et al while using it in self-compacting concrete [22]. Riaz et al carried out a similar study, involving the use of a fine filler material in place of clay in fire-burnt clayey bricks: They have observed similar increase in compressive strength of the finished blocks [23].…”
Section: Resultsmentioning
confidence: 72%
“…It has been shown that, while reducing the environmental footprint, the addition of up to 30% of waste calcium carbonate does not negatively affect the materials’ properties (Valentini et al , 2020). Marble waste from Tunisian quarries has been used previously in the preparation of self-compacting concrete (Alyousef et al , 2018). Considering that marble production in Tunisia represents an important industrial sector (Ministry of Industry and SMEs, Republic of Tunisia, 2014) and that up to 60% of the gross production of waste occurs during marble quarrying, polishing and processing (Montani, 2017), the addition of this waste has potential for the development of sustainable binders based on locally sourced raw materials through adopting a circular economy approach.…”
Section: Experimental Methods and Materials Characterizationmentioning
confidence: 99%
“…Figure 5 presents the compressive strength development of the ACM with WMD. With the increase of the WMD content up to 15%, compressive strength decreases due to a lack of participation in the hydration process [37].…”
Section: Properties Of Hardened Mortarsmentioning
confidence: 99%